Unusual magneto-thermal properties in Sr4Ru3O10. (14th February 2017) - Kumar, Pramod; Kumar, Naresh; Kumar, Rachana
Abstarct: In the present, we have studied the magneto-thermal and magneto-transport properties in single crystalline Sr4 Ru3 O10 for for both H // ab and H // c plane. Sr4 Ru3 O10 metamagnetic transitions have also studied with the help of Arrot's plot, which shows that there a metamagnetic transition which the presence of two electronic states in Sr4 Ru3 O10 .